MENDAMAIKAN KEBERAGAMAN MELALUI PENGUATAN TOLERANSI DAN KERUKUNAN ANTAR KOMUNITAS MULTI AGAMA - Ritonga, A. Rahman (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
Indonesia is a multicultural country, has a diverse religions, ethnic groups and races. Therefore, Indonesia is known as a country prone to conflict. SARA issues are often manipulated to disrupt national unity, such as the Ahmadiyah issue, the case of Ambon, suicide bombings, GKI Yasmin and so on. Islam taught that the difference is one of the realities of life and one of God’s laws that is not worthy of debate. Hence, the important thing that has to be a priority in the difference is to benefitted the positive aspects by removing the negative aspects. The positive aspects should be prioritized and managed with the principles of mutual respect, solidarity, fraternity, openness and togetherness as well as empowering available local knowledge.